Effectiveness of resistance inductors for potato late blight management in Peru - Sanabria, K.; Pérez, W.; Andrade-Piedra, J.L. (Elsevier, 2020)
We studied the effectiveness of resistance inductors (RIs) to control potato late blight (LB) in Peru. Plants of susceptible cultivar Yungay were sprayed separately with each of the following RIs: Potassium phosphite, aluminum lignosulfonate, organics acids, and silicon oxide, and then inoculated with Phytophthora infestans in laboratory and greenhouse conditions in Lima. Potassium phosphite and aluminum lignosulfonate were then tested in field trials using four potato cultivars with different levels of susceptibility to LB in three locations in the central highlands of Peru during the wet season. They were tested either alone, in alternation with each other, or in alternation with the contact fungicide propineb. Other treatments were propineb alone; spraying based on a decision support tool using systemic (propamocarb + fluopicolide; dimethomorph + mancozeb) and/or contact fungicide (propineb); and a control treatment without fungicides. Disease severity, commercial yield and environmental impact (EI) were assessed in all experiments. The most effective treatments depended on the susceptibility of the potato cultivar. In the susceptible cultivars Canchan and Yungay, the best treatments were potassium phosphite and propineb (alone or alternated); in the moderately resistant cultivar UNICA, the best treatments were potassium phosphite, and aluminum lignosulfonate alternated with propineb, and propineb alone; and in the resistant cultivar Serranita, all treatments were effective to control LB. Since potassium phosphite has very low environmental impact quotient, these results showed that it is possible to control LB in an environmental-friendly manner using RIs, even in susceptible cultivars during the wet season in the highlands of Peru.